PERBEDAAN TINGKAT ASUPAN ENERGI SERTA GLUKOSA DARAH SEBELUM DAN SESUDAH PROSES ASUHAN GIZI TERSTANDAR PADA PASIEN DIABETES MELITUS TIPE 2 Difference of Energy Intake and Blood Glucose Level Before and After Providing Standardized Nutrition Care Process in Type 2 Diabetes Mellitus Patients - Arizta Primadiyanti; Novilla Anindya Permata; Andina Devi Arvita; Rosidah Inayati; Dian Handayani (Universitas Airlangga, 2020)
The provision of nutrition care process (NCP) in diabetes mellitus (DM) patients is very important in determining the patient's diet to control blood glucose and to prevent complications. This study aimed to determine the diff erences in levels of intake and blood glucose levels before and after the implementation of NCP for type 2 DM (T2DM) inpatients of RSUD Dr. Saiful Anwar Malang. The design of this study was cross sectional, using secondary data sources from 32 patient medical records consisting of data on age, gender, nutritional status, complications of disease, nutritional diagnosis, nutritional intervention, energy intake, and blood glucose level. The analysis test used was the T-test dependent test on the normal data distribution and the Wilxocon test on the abnormal data distribution. The results of this study indicate a diff erence in the level of after and before intake (p = 0.020) with an increase in the average intake of 65.75 ± 18.23% to 75.50 ± 17.69% of the total energy needs. The analysis of blood glucose before and after showed p = 0.023, which means that there were diff erences in blood glucose before and after the NCP implementation. Blood glucose results showed an average decrease of 205 ± 93.85 mg/dl to 155.9 ± 50.53 mg/dl. The results of this study showed that there were diff erences in levels of energy intake and blood glucose levels before and after the provision of NCP by dietitians/nutritionists.